2021
DOI: 10.1111/jcpe.13444
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, radiographic and economic evaluation of short‐6‐mm implants and longer implants combined with osteotome sinus floor elevation in moderately atrophic maxillae: A 3‐year randomized clinical trial

Abstract: Aim: To compare the 3-year clinical, radiographic and economic outcomes of short-6-mm implants and longer implants combined with osteotome sinus floor elevation (OSFE) in the posterior maxilla. Material and Methods:This study enrolled 225 patients (225 implants with diameter of 4.1 mm and 4.8 mm) with a posterior maxillary residual bone height (RBH) of 6-8 mm. Patients were randomly divided into three groups: Group 1 (6 mm implants alone), Group 2 (8 mm implants + OSFE) and Group 3 (10 mm implants + OSFE). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 20 publications
(29 reference statements)
0
36
0
Order By: Relevance
“…After removing 710 duplicates, titles and abstracts of the remaining 1174 articles were screened. The full texts of nine potentially eligible articles were browsed; three studies that met the inclusion criteria were selected for the final analysis [ 26 28 ]. Figure 1 describes the reasons why studies were removed from the review.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After removing 710 duplicates, titles and abstracts of the remaining 1174 articles were screened. The full texts of nine potentially eligible articles were browsed; three studies that met the inclusion criteria were selected for the final analysis [ 26 28 ]. Figure 1 describes the reasons why studies were removed from the review.…”
Section: Resultsmentioning
confidence: 99%
“…This review included three RCTs [ 26 28 ], and Table 2 outlines their characteristics. The length of short implants ranged from 6.5 to 8 mm, and that of standard implants ranged from 10 to 16 mm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The heterogeneity was considered high for the marginal bone loss (I 2 = 78% and I 2 = 74%), so funnel plot shows asymmetry. The main reason of the asymmetry encountered could be due to the difference in the sample size of the included studies Implant diameters, in the present research, ranged from 3.3 [42] to 6 mm [5]. Differences in implant diameter introduced heterogeneity among studies with respect to MBL.…”
Section: Discussionmentioning
confidence: 85%
“…Most of the studies reported comparable survival rates of 8‐mm implants and longer implants (Nielsen et al, 2019). As for 6‐mm implant, several mid‐term data (3 to 5 years) revealed acceptable clinical results (Gulje et al, 2021; Naenni et al, 2018; Shi et al, 2021). It is suggested that time in function may influence the survival rate of short implants more than that of longer implants (Jung et al, 2018).…”
Section: Introductionmentioning
confidence: 99%